The Fracture Behavior and Thermal Stability of Commercially Pure Nickel Sheets Processed by Constrained Groove Pressing - Zongshen Wang; Yanjin Guan; Lin Li; Lihua Zhu (Metals, 2019)
Constrained groove pressing (CGP) is one of the most promising severe plastic deformation (SPD) techniques suitable for producing ultra-fine grained (UFG) sheet or plane metallic materials with unique physical, chemical, and mechanical properties. However, the heavily deformed sheets are usually with high strength but low ductility due to work hardening and micro-cracking, and the UFG microstructure and high strength are unstable especially when exposed to high temperatures. Thus, in this work, CGP was conducted on commercially pure nickel sheets and, firstly, the fracture mechanism of the processed sheets was examined. Then, the annealing behavior of CGP nickel sheets was investigated in detail to explore their thermal stability and improve their ductility. The results showed that significant grain refinement and strength improvement of the nickel sheets were achieved with great loss of ductility. The fracture surface morphology of the sheet sample exhibited typical characteristics of fatigue fracture, and inhomogeneous strain distribution and work hardening determined the micro-crack initiation position and propagation direction. The CGP sheets by one and two passes showed high thermal stability up to 650 and 600 °C, respectively, owing to different stored internal stresses and accumulated energy. In both cases, obvious recovery of elongation to failure from 12.7% and 10.6% to 29.3% and 27.3% were achieved by CGP with post-deformation annealing treatment, respectively, with acceptable drop of strength.